THU0689 ASTHMA AND ELEVATION OF ANTI-CITRULLINATED PROTEIN ANTIBODIES PRIOR TO THE ONSET OF RHEUMATOID ARTHRITIS. (June 2019) - Zaccardelli, Alessandra; Liu, Xinyi; Ford, Julia; Tedeschi, Sara; Cui, Jing; Lu, Bing; Chu, Su; Schur, Peter; Speyer, Cameron; Costenbader, Karen; Robinson, William; Sokolove, Jeremy; et al.
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are central to RA pathogenesis, with serum ACPA titers elevated years prior to clinical RA onset. Aberrant protein citrullination may occur in inflamed airway mucosa, forming neoantigens producing ACPA before articular involvement. Thus, individuals with inflammatory airway diseases, such as asthma, may be susceptible to RA-related autoimmunity. Objectives: To investigate asthma as a risk factor for ACPA+ in serum prior to clinical RA onset. Methods: We performed a cross-sectional analysis among women in the Nurses' Health Studies to examine whether asthma was associated with pre-RA ACPA+. Incident RA cases occurring after blood draw met research criteria and were each matched to 3 controls by age and menopausal status. Presence of self-reported asthma and potential confounders, including smoking pack-years, were assessed using questionnaires. The sensitive (primary) definition for ACPA+ was: >3 units on CCP2 or elevation (>99th percentile of the control distribution) on a research assay composed of autoantibodies targeting specific citrullinated protein epitopes. The specific (secondary) definition for ACPA+ was: >5 units on CCP2 or elevation of ≥2 different antibodies to citrullinated proteins on the research assay. Logistic regression was used to obtain ORs for ACPA+ independent of confounders. We performed secondary analyses using the specific definition for ACPA+ and in subgroups restricted to never smokers and pre-RA cases. Results: We measured ACPA on 1, 135 women, including 286 pre-RA cases. Serum was banked a mean of 9.7 years (SD 5.8) prior to RA diagnosis, mean age of 51.9 years (SD 7.9). Overall, 12% of pre-RA cases reported asthma compared to 7% of controls; pre-RA cases were heavier smokers than controls. Of pre-RA cases, 96 (34%) were ACPA+ by the sensitive definition and 60 (21%) by the specific definition. Among the entire sample, women with asthma were more likely to have ACPA+ (unadjusted OR 2.51, 95%CI 1.42-4.44) compared to those without asthma. After adjusting for age, smoking, BMI, and time to RA/matched date, asthma remained significantly associated with ACPA+ (OR 2.32, 95%CI 1.29-4.16). In the secondary analyses, we found similar associations of asthma with ACPA+ when using the specific definition for ACPA+ (multivariable OR 2.28, 95%CI 1.11-4.69) and when restricted to never smokers (OR 3.11, 95%CI 1.29-7.47) and only pre-RA cases (OR 2.22, 95%CI 1.01-4.88). Conclusion: Asthma may be a novel risk factor for elevation of ACPA prior to RA onset, independent of smoking. These findings encourage further research on the contribution of airway inflammation to RA pathogenesis. Disclosure of Interests:  : Alessandra Zaccardelli: None declared, Xinyi Liu: None declared, Julia Ford: None declared, Sara Tedeschi: None declared, Jing Cui: None declared, Bing Lu: None declared, Su Chu: None declared, Peter Schur: None declared, Cameron Speyer: None declared, Karen Costenbader: None declared, William Robinson: None declared, Jeremy Sokolove Shareholder of: AbbVie, Employee of: AbbVie, Carlos Camargo, Jr.: None declared, Jeffrey Sparks Grant/research support from: Bristol-Myers Squibb, Amgen, Consultant for: Optum